Features of the Presentation of Grammatical Material by Using Problem-Based Technology - Kadirova Miyassar Artekovna (Researchparks Publishing, 2021)
the article deals with the issues based on the essence and features of the application of the methodology of problem learning, its essence, the main methods and functions, the methodology for organizing problem learning and the requirements that modern standards impose on it, in order to determine what role problem learning methods can and should play in modern education system and the process of using problem-based technology in the presentation of grammatical material.